Modulation of Aβ42 Fibrillation in the Presence of Vitamin A Metabolite: Insights from Molecular Dynamics Simulations - Gupta, Vibhuti (My University, 2024)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by misfolding and consequent aggregation of amyloid-β (Aβ) protein, resulting in the formation of amyloid plaques within the brain. The best possible therapy approach for AD treatment is to prevent Aβ aggregation. Joshi et al. evaluated 18 fat-soluble and water-soluble vitamins and reported vitamin A metabolite (retinoic acid) significantly inhibited Aβ42 aggregation. Thioflavin T (ThT) fluorescence analysis depicted a concentration-dependent decrease in both the primary and secondary nucleation process of Aβ42 on the inclusion of retinoic acid. Moreover, dynamic light scattering (DLS) analysis did not depict the presence of large assemblies for retinoic acid alone. Co-incubation of Aβ42 oligomer with retinoic acid notably increased the cell viability to 97 ± 6% highlighting reduction of cytotoxicity of Aβ42 oligomers by retinoic acid. Besides extensive experimental research, the molecular interactions and binding mechanism behind the inhibitory potential of retinoic acid on Aβ42 aggregation is still unknown. Thus, computational techniques to investigate the molecular mechanism in which retinoic acid blocks self-fibrillation of Aβ42 aggregation were performed. The molecular docking result highlighted favourable binding of retinoic acid with Aβ42 monomer having binding energy ̶ 6.10 kcal mol-1. The RMSD and RMSF analyses depicted reduced conformational fluctuations in Aβ42 monomer on the addition of retinoic acid. Notably, an increase in helix content was observed in the Aβ42 monomer from 44.80 ± 2.20 to 54.40 ± 0.88% which depicted reduced aggregation propensity of Aβ42 monomer in the presence of retinoic acid. Moreover, the average number of intramolecular hydrogen bonds was increased from 19.10 ± 0.96 to 21.07 ± 1.05 on the incorporation of retinoic acid, which confirms the increase in the helical conformation of Aβ42 monomer. PCA, FEL, and conformational clustering analyses depicted enhanced conformational homogeneity of Aβ42 monomer-retinoic acid complex. The binding free energy analysis (ΔGbinding= –54.89 ± 14.07 kJ mol-1) indicated favourable binding of retinoic acid with Aβ42 monomer. Additionally, binding of central hydrophobic core (CHC) residues Leu17 (–5.95 kJ mol-1), Phe20 (–6.19 kJ mol-1), and Ala21 (–3.53 kJ mol-1) of Aβ42 monomer to retinoic acid highlighted the lower aggregation tendency of Aβ42 monomer. The molecular insights into binding interactions of retinoic acid to Aβ42 peptide will be beneficial for designing new potent inhibitors as a therapeutic approach against AD.
Keywords: Alzheimer’s disease; amyloid-β peptide; vitamin A metabolite; molecular dynamics